KONSELING MULTIKULTURAL SEBUAH PARADIGMA BARU UNTUK ABAD BARU - MUHAMMAD YUSUF (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2016)
Basically this research is a translation of the book entitled Multicultural Issues in Counseling: New Approaches to Diversity in the first section presented by Courtland C. Lee and Cara J. Ramsey. However, the researcher tried to expand with the other references equally examine about counseling in the cultural context. As we know that, Indonesian society are rich of cultures, such as: ethical, tribes, and races so that the researcher considered the cultural studies in the implementation of counseling process was a significant thing in order to help the counselors in understanding the counselee problem widely